2021
DOI: 10.1007/s00216-020-03137-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of the surface ligand on the performance of electrochemical SARS-CoV-2 antigen biosensors

Abstract: Point-of-care (POC) technologies and testing programs hold great potential to significantly improve diagnosis and disease surveillance. POC tests have the intrinsic advantage of being able to be performed near the patient or treatment facility, owing to their portable character. With rapid results often in minutes, these diagnostic platforms have a high positive impact on disease management. POC tests are, in addition, advantageous in situations of a shortage of skilled personnel and restricted availability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 48 publications
(37 reference statements)
1
25
0
Order By: Relevance
“…This sensing sensitivity of the maleimide-thiol aptamer sensor is comparable to other electrochemical ( Saroglia et al, 2021 , Szunerits et al, 2021 , Zhang et al, 2020 ) and electrical ( Seo et al, 2020 ) sensors reported thus far in the literature. In addition, the possibility of detecting the variants 20I/501Y.V1(called “British variant”) and 20H/501Y.V2 (called “South African variant”) was investigated by using SARS-CoV-2 variant isolates.…”
Section: Resultssupporting
confidence: 84%
“…This sensing sensitivity of the maleimide-thiol aptamer sensor is comparable to other electrochemical ( Saroglia et al, 2021 , Szunerits et al, 2021 , Zhang et al, 2020 ) and electrical ( Seo et al, 2020 ) sensors reported thus far in the literature. In addition, the possibility of detecting the variants 20I/501Y.V1(called “British variant”) and 20H/501Y.V2 (called “South African variant”) was investigated by using SARS-CoV-2 variant isolates.…”
Section: Resultssupporting
confidence: 84%
“…Spike protein is repeated 50–200 times on the viral surface [ 42 ] and consists of approximately 1273 amino acids [ 43 ], of which around 200 correspond to the RBD region (amino acid residues 331–524) located in the S1 subunit of the protein [ 44 ]. ACE2 is a protein of 805 amino acids formed by the N-terminal peptidase and the C-terminal choleric domains.…”
Section: Resultsmentioning
confidence: 99%
“…This sensor was able to detect COVID-19 in a couple of patients, and the results were comparable to that of commercial ELISA. The responses are monitored with square-wave voltammetry [141][142][143]. In other electrochemical detection applications, it was demonstrated that SARS-CoV-2 can be detected in saliva.…”
Section: Electrochemical Biosensormentioning
confidence: 99%